2017
DOI: 10.1002/jso.24602
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with local recurrence in operated osteosarcomas: A retrospective evaluation of 95 cases from a tertiary care center in a resource challenged environment

Abstract: Lack of financial resources and availability of few tertiary care centers dealing with musculoskeletal oncology in the developing countries, lead to overburden with a long waiting list for tumor surgery making the scenario different from the Western world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Biopsy/tumor resection performed by different centers in this study is a significant predictor of the development of local recurrence and poorer overall survival. This is similar to the reports by Picci et al [66], Andreou et al [6], and Poudel et al [39]. The biopsy approach must be planned so that it can be completely and widely excised at the moment of the resection.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Biopsy/tumor resection performed by different centers in this study is a significant predictor of the development of local recurrence and poorer overall survival. This is similar to the reports by Picci et al [66], Andreou et al [6], and Poudel et al [39]. The biopsy approach must be planned so that it can be completely and widely excised at the moment of the resection.…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of local recurrence (LR) in this study was 13.7% (25/182), and the 5-year LR-free survival was 85.3 ± 5.3%. Our local recurrence rate of 13.7% is slightly higher than that presented in some reported data [6, 12, 37, 38], but these data are equal to data from a larger series report [2, 8, 3941].…”
Section: Discussioncontrasting
confidence: 63%
“…*p = 0.009; †p = 0.025. treating patients with osteosarcoma. Although many authors have studied the prognostic factors for LRFS or OS in osteosarcoma, 1,8,9,[15][16][17][18][19][20][21][22]24,[31][32][33][34][35][36][37] there has been no study focusing specifically on the prognostic significance of the vascular proximity of the tumour. Previous studies have demonstrated that the most important predictive factors regarding LR were poor response to neoadjuvant chemotherapy and inadequate surgical margins, 21,22 and those regarding OS were age, tumour size, tumour location, response to neoadjuvant chemotherapy, and pathological fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the most important predictive factors regarding LR were poor response to neoadjuvant chemotherapy and inadequate surgical margins, 21,22 and those regarding OS were age, tumour size, tumour location, response to neoadjuvant chemotherapy, and pathological fracture. 8,[15][16][17][18][19][20]35 However, several discrepancies have been observed between the various cohorts studied 21,22,31,32,37 and Bramer et al 35 concluded that this might be explained by methodological issues. In our study, the most important prognostic factors for LRFS were the tumour's response to neoadjuvant chemotherapy and also the presence of vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, deferring surgery for a later date can significantly increase the risk of recurrence of these tumours. Poudel et al 10 had studied the risk factors associated with local recurrence of Osteosarcoma and had reported that each week delay in surgery after completion of neo‐adjuvant chemotherapy increases recurrence risk by 1.14 times. Also, at a mean follow‐up of 2.8 years, just 20% patients with recurrence were surviving as against 60% of survivors in the group without local recurrence.…”
Section: Discussionmentioning
confidence: 99%